Effects of Roasting Level and Milk Addition on In Vivo Aroma Release and Perception of Coffee - Cleve, Nina; Gonzalez-Estanol, Karina; Khomenko, Iuliia; Pedrotti, Michele; Cappellin, Luca; Biasioli, Franco; Beauchamp, Jonathan (Journal of Agricultural and Food Chemistry, 2025)
Adding milk to coffee balances its flavor and reduces unpalatable notes (e.g., burnt aroma, bitterness), but research on how adding milk affects in vivo aroma release and perception is limited. This study analyzed the impact of adding cow or oat milk (30% w/w) on in vivo aroma release and flavor perception in medium and dark roasted Arabica coffees. Temporal dominance of sensations showed that medium roast had bitter and roasted flavors, while bitter and burnt flavors dominated the dark roast. The milks elicited their own inherent notes (dairy-like or caramel-like/vanilla-like) and decreased the perception of coffee-related flavors. Aroma release analysis by proton transfer reaction-mass spectrometry provided data on 47 volatiles, with quantitative differences between roasting levels being indicative of the changes in perception. While milk addition strongly affected perception, it did not systematically affect in vivo release of coffee-related volatiles, highlighting the challenges in aligning analytical and sensory data sets.
CRIS-Team Scopus Importer:2025-05-30
Keywords: flavor; oat milk; plant-based alternative; proton transfer reaction-mass spectrometry (PTR-MS); temporal dominance of sensations (TDS); volatiles